2021
DOI: 10.3389/fmicb.2021.663020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Multidrug-Resistant Pseudomonas aeruginosa Isolates Carrying blaVIM–2 and blaKPC–2 Genes That Spread on Different Genetic Environment in Colombia

Abstract: Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen with an increase in the frequency of infections caused by multidrug resistant (MDR) and extensively drug resistant (XDR) strains, limiting the available therapeutic options. The most troublesome resistance is the acquisition and production of carbapenemases such as Verona integron-encoded metallo-β-lactamases (VIM), the most frequent and widespread, and the Klebsiella pneumoniae carbapenemases (KPC), which has continuously spread in the last dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Of note, seven (9.5%) isolates from Colombia carried simultaneously KPC and VIM carbapenemases. Our group identified P. aeruginosa isolates co-harboring KPC and VIM for the first time in 2012, and according to local surveillance studies, strains co-producing these two carbapenemases and belonging to different STs have continuing spreading throughout the country ( Villegas et al, 2007 ; Vanegas et al, 2014 ; Pacheco et al, 2019 ; Rada et al, 2021 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Of note, seven (9.5%) isolates from Colombia carried simultaneously KPC and VIM carbapenemases. Our group identified P. aeruginosa isolates co-harboring KPC and VIM for the first time in 2012, and according to local surveillance studies, strains co-producing these two carbapenemases and belonging to different STs have continuing spreading throughout the country ( Villegas et al, 2007 ; Vanegas et al, 2014 ; Pacheco et al, 2019 ; Rada et al, 2021 ).…”
Section: Discussionmentioning
confidence: 87%
“…ESBLs have also been associated with decreased susceptibility to TOL. Indeed, ESBLs such as GES-like, PER-1, BEL-1, BEL-2, and VEB-1, and some OXA enzymes like OXA-2 variants, OXA-10, and OXA-14 can significantly affect the efficacy of TOL ( Vanegas et al, 2014 ; Rada et al, 2021 ). In this study only two isolates, one from Argentina and one from Chile were found to carry PER-1 and PER-3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… P. aeruginosa strains belonging to ST313 were widely disseminated across different continents ( 25 ). They have been described as intestinal colonizers in healthy individuals but were rarely reported from the poultry farm environment ( 26 ).…”
Section: Observationmentioning
confidence: 99%
“…Even more, after the misuse highly promoted during the COVID-19, an increase in antimicrobial resistance, is not only expected, but already observed in many countries, including Colombia 41,42 . The fight against antimicrobial resistance, promotion of antimicrobial stewardship programs and education, are key in this context [43][44][45][46] .…”
Section: Retos Y Visiones Para Las Enfermedades Infecciosas Enmentioning
confidence: 99%